Laryngeal mask airway versus other airway devices for anesthesia in children with an upper respiratory tract infection: A systematic review and metaanalysis of respiratory complications - De Carvalho, Ana Lygia R. [UNESP]; Vital, Roberto B. [UNESP]; De Lira, Carlos C.S. [UNESP]; Magro, Igor B. [UNESP]; Sato, Patrícia T. S. [UNESP]; Lima, Laís H. N. [UNESP]; Braz, Leandro Gobbo [UNESP]; Módolo, Norma S. P. [UNESP] (Wolters Kluwer, 2018)
There is an association between upper respiratory tract infection (URTI) and an increased incidence of perioperative respiratory adverse events (PRAEs), which is a major risk for morbidity during pediatric anesthesia. The aim of the present study was to compare the risk of PRAEs among different airway devices during anesthesia in children with a URTI. A systematic review according to the Cochrane Handbook and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was conducted. Only randomized clinical trials evaluating anesthesia in children with a URTI and who were submitted to any of the airway devices were included. From 1030 studies identified, 5 randomized clinical trials were included in the final analysis. There were no statistical differences between laryngeal mask airway (LMA®) and endotracheal tube (ETT) regarding breath holding or apnea (risk ratio [RR], 0.82; 95% confidence interval [CI], 0.41-1.65), laryngospasm (RR, 0.74; 95% CI, 0.18-2.95), and arterial oxygen desaturation (RR, 0.44; 95% CI, 0.16-1.17). The quality of evidence was low for the first outcome and very low for the 2 other outcomes, respectively. The LMA use produced a significant reduction of cough (RR, 0.75; 95% CI, 0.58-0.96, low quality of evidence) compared with ETT. The ideal airway management in children with a URTI remains obscure given that there are few data of perioperative respiratory complications during anesthesia. This systematic review demonstrates that LMA use during anesthesia in children with URTI did not result in decrease of the most feared PRAEs. However, LMA was better than ETT in reducing cough. Further research is needed to define the risks more clearly because cough and laryngospasm have similar triggers, and both bronchospasm and laryngospasm trigger cough.